Effects of early palliative care on patients with incurable cancer: A meta‐analysis and systematic review. (25th May 2022) - Huo, Bingjie; Song, Yanru; Chang, Liang; Tan, Bibo
Abstract: Objective: This meta‐analysis aims to compare the effects of early palliative care on patients with incurable cancer with those of standard oncologic care or on‐demand palliative care. Methods: Pubmed, Embase, Web of Science, Cochrane Library, ClinicalTrials.gov and World Health Organization International Clinical Trials Registry Platform (ICTRP) were searched for relevant randomised controlled trials. We also screened reference lists of included studies for additional qualified studies. We used Cochrane Collaboration Risk of Bias Tool to evaluate quality of included studies. DerSimonian and Laird's random effects meta‐analysis was used to synthesise the effects. Results: Sixteen in 1376 studies were included. The pooled data suggested that patients receiving early palliative care had better quality of life (SMD = 0.737, 95% CI: 0.240–1.234), fewer symptoms (SMD = 0.304, 95% CI: 0.097–0.510), better mood (SMD = −0.443, 95% CI: −0.605 to −0.282), better survival (hazard ratio [HR] of death: HR = 1.521, 95% CI: 1.521–1.923; 1‐year overall survival probability: HR = 1.238, 95% CI: 1.031–1.486) and higher probability of dying at home (HR = 1.153, 95% CI: 1.027–1.295) than patients in the control group. And there is no difference between resource use. Conclusion: Early palliative care improves lives of patients with incurable cancer, but the evidence level is low because of high heterogeneity of quality of life and small numbers of included studies for other results.